Pengaruh Pemberian Buah Nanas (Ananas Comosus L. Merr) terhadap Tingkat Keempukan, Organoleptik dan Uji Fisik Daging Kerbau - Adelia Adelia; Kurniawan Sinaga (Pusat riset dan Inovasi Nasional, 2025)
This study aims to encourage the effect of adding pineapple (Ananas Comosus L. Mer) in the marinating process on the level of tenderness, organoleptic, physical quality and protein content of buffalo meat. The method used is an experiment with a completely randomized plan (CRD), consisting of four treatments, namely: PO (without pineapple), P1 (250 g pineapple), P2 (500 g pineapple) and P3 (750 g pineapple). The results showed that the addition of pineapple significantly affected the quality of buffalo meat. The color of the meat became brighter with increasing pineapple levels while the texture of buffalo meat became more tender due to the bromelain enzyme which breaks down collagen. Organoleptic parameters using the Kruskal Wallis Test showed a significant difference in the level of tenderness, color, texture, aroma and taste in each treatment, although excessive use of pineapple produced a dominant sour taste. The protein content of buffalo meat changed due to the proteolysis process influenced by the bromelain enzyme. This study indicates that marinating buffalo meat using pineapple can improve the quality of buffalo meat physically, organoleptically and nutritionally.